Visualizing Words: The Effectiveness of Colored Pictures in Teaching Vocabulary - Andriani, Nita; Hastini; Bochari3, Siska; Mertosono4, Sudarkam R. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study uniquely explores the combined impact of colored pictures and student motivation on vocabulary mastery, an intersection rarely examined. This research investigates the effectiveness of colored pictures as a teaching medium and the role of student motivation in improving vocabulary comprehension among eighth-grade students at SMPN 19 Palu. A quasi-experimental design was employed, including 55 pupils split into two groups: a control group (n = 27) and an experimental group (n = 28). The experimental group was taught using colored pictures, whereas the control group followed conventional methods of instruction. Vocabulary mastery was assessed through Tests before and after, and students' motivation was measured using a Likert-scale questionnaire. The findings revealed that the experimental group outperformed the control group by a substantial margin, achieving an average post-test score of 72.92, compared to 61.46 in the control group. There was a statistically significant change (p < 0.05), demonstrating the effectiveness of colored pictures in enhancing vocabulary mastery. Moreover, students with higher motivation in the experimental group was successful. Superior scores, with average of 75.30, compared to 69.10 for those with moderate motivation. These results confirm that colored pictures not only enhance vocabulary acquisition but also boost student engagement and motivation. The study suggests that integrating colored pictures into teaching strategies is a valuable approach to improving vocabulary mastery and fostering a more engaging setting for learning. For educators and legislators looking to improve vocabulary mastery results in language instruction, these studies provide useful insights.